1994
DOI: 10.2307/282461
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator Mass Spectrometry (AMS) Dates Confirm Early Zea Mays in the Mississippi River Valley

Abstract: Two accelerator mass spectrometry (AMS) dates obtained from samples of Zea mays from the Holding site, 11MS118, in the American Bottom near East St. Louis, Illinois, establish the presence of maize in the Mississippi Valley between 170 B.C. and A.D. 60. The dates finally establish the occurrence of Middle Woodland maize in Illinois and are the earliest dates thus far for maize east of the Mississippi River. Other reports of early Middle Woodland maize in the Midcontinent region should not be discounted unless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Similarly, the recent direct AMS dating of the arrival of maize in the southwestern United States at about 2000 1500 cal B.C. (Wills 1995), and in the eastern United States by cal A.D. 1 (Riley et al 1994) appear compatible with the AMS dates that mark the arrival of maize in Tamaulipas at about 2500 cal B.C., and the initial appearance of this domesticate in Tehuacan at 3500 cal B.C. (Long et al 1989).…”
Section: Slcerarlamentioning
confidence: 60%
“…Similarly, the recent direct AMS dating of the arrival of maize in the southwestern United States at about 2000 1500 cal B.C. (Wills 1995), and in the eastern United States by cal A.D. 1 (Riley et al 1994) appear compatible with the AMS dates that mark the arrival of maize in Tamaulipas at about 2500 cal B.C., and the initial appearance of this domesticate in Tehuacan at 3500 cal B.C. (Long et al 1989).…”
Section: Slcerarlamentioning
confidence: 60%
“…The importance of maize in Central America (DeNiro & Epstein, 1981;White & Schwarcz, 1989), North America (Riley et al, 1994;Larsen et al, 1992) and South America (van der Merwe et al, 1981;Burger & van der Merwe, 1990) has been confirmed by stable isotope studies. There are also studies indicating the importance of C 3 plants in post-Neolithic diets in coastal Europe, associated with a move away from marine foods (Tauber, 1981;Richards & Hedges, 1999;Lubell et al, 1994), as well as preliminary studies indicating the importance of millet in China (Cai & Qui, 1984) and rice in Japan (Chisholm & Koike, 1996).…”
Section: Dietary Changes At the 'Neolithic Revolution'mentioning
confidence: 74%
“…Although maize has been found in Middle Woodland contexts in the Eastern Woodlands (Riley et al, 1994;Smith, 1989), its first appearance at archaeological sites in this region occurs well into the Late Woodland period, at about AD 580 (Asch and Asch, 1985b). Carbon isotope analyses demonstrate that maize is not a measurable part of the diet until after AD 800 (Bender et al, 1981;Buikstra et al, 1987;van der Merwe and Vogel, 1978).…”
Section: The Later Late Woodland Period: the Adoption Of Maize As A Dmentioning
confidence: 99%